Plasticized polymer electrolytes for alkaline batteries / Razi Unuh - Unuh, Razi (2007)
Plasticized polymer electrolytes comprise of poly(vinyl alcohol) (PVA), potassium hydroxide (KOH) as ionic dopant, propylene carbonate (PC) as plasticizer and distill water as a solvent have been prepared by solution casting technique. The concentration of KOH and the amount of PC was varied systematically. The conductivity was studied using a.c impedance spectroscopy to determine the ionic conductivity in sample PVA + KOH and PVA + KOH + PC. The conductivity was calculated using bulk impedance value in the frequency range from 100Hz to 1MHzat room temperature. The highest conductivity for sample PVA + KOH was 4.52 xlO-04 S/cm when 2M KOH was added and the value was enhanced upon the additional of PC. The highest conductivity was 1.80 x 10'2 S/cm when the sample was added with 10% PC. Electrochemical cell of Zn |PVA + KOH + 10%PC| Mn04was fabricated and the open circuit voltage (OCV) showed decreasing from 1.063 V to 0.590 V and remained constant for 24 hours.